Enhancing the Effectiveness of Significant Event Analysis: Exploring Personal Impact and Applying Systems Thinking in Primary Care. Issue 3 (2016) - Bowie, Paul; McNaughton, Elaine; Bruce, David; Holly, Deirdre; Forrest, Eleanor; Macleod, Marion; Kennedy, Susan; Power, Ailsa; Toppin, Denis; Black, Irene; Pooley, Janet; Taylor, Audrey; et al.
Abstract : Introduction: Significant event analysis (SEA) is well established in many primary care settings but can be poorly implemented. Reasons include the emotional impact on clinicians and limited knowledge of systems thinking in establishing why events happen and formulating improvements. To enhance SEA effectiveness, we developed and tested "guiding tools" based on human factors principles. Methods: Mixed-methods development of guiding tools (Personal Booklet—to help with emotional demands and apply a human factors analysis at the individual level; Desk Pad—to guide a team-based systems analysis; and a written Report Format) by a multiprofessional "expert" group and testing with Scottish primary care practitioners who submitted completed enhanced SEA reports. Evaluation data were collected through questionnaire, telephone interviews, and thematic analysis of SEA reports. Results: Overall, 149/240 care practitioners tested the guiding tools and submitted completed SEA reports (62.1%). Reported understanding of how to undertake SEA improved postintervention ( P < .001), while most agreed that the Personal Booklet was practical (88/123, 71.5%) and relevant to dealing with related emotions (93/123, 75.6%). The Desk Pad tool helped focus the SEA on systems issues (85/123, 69.1%), while most found the Report Format clear (94/123, 76.4%) and would recommend it (88/123, 71.5%). Most SEA reports adopted a systems approach to analyses (125/149, 83.9%), care improvement (74/149, 49.7), or planned actions (42/149, 28.2%). Discussion: Applying human factors principles to SEA potentially enables care teams to gain a systems-based understanding of why things go wrong, which may help with related emotional demands and with more effective learning and improvement.